2013
DOI: 10.1371/journal.pone.0078381
|View full text |Cite
|
Sign up to set email alerts
|

miR-582-5p Is Upregulated in Patients with Active Tuberculosis and Inhibits Apoptosis of Monocytes by Targeting FOXO1

Abstract: Macrophage apoptosis is a host innate defense mechanism against tuberculosis (TB). In this study, we found that percentage of apoptotic cells in peripheral blood monocytes from patients with active TB was lower than that from healthy controls (p<0.001). To understand whether microRNAs can modulate apoptosis of monocytes, we investigated differentially expressed microRNAs in patients with active TB. miR-582-5p was mainly expressed in monocytes and was upregulated in patients with active TB. The apoptotic percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 29 publications
4
45
0
Order By: Relevance
“…The high count of peripheral monocytes also observed in the TB contacts prior to progression to an active TB in the present study is consistent with the hypothesis that this could be a biomarker for progressive TB [42,43], and our study suggests that this is the case even before the appearance of symptoms.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The high count of peripheral monocytes also observed in the TB contacts prior to progression to an active TB in the present study is consistent with the hypothesis that this could be a biomarker for progressive TB [42,43], and our study suggests that this is the case even before the appearance of symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…It has already been reported that patients with active TB have an increased frequency of peripheral blood monocytes compared to healthy individuals, and this study and others have shown that effective anti-TB chemotherapy can reverse this [17,41,42]. The high count of peripheral monocytes also observed in the TB contacts prior to progression to an active TB in the present study is consistent with the hypothesis that this could be a biomarker for progressive TB [42,43], and our study suggests that this is the case even before the appearance of symptoms.…”
Section: Discussionsupporting
confidence: 58%
“…However, with some exceptions (17,(30)(31)(32)(33)(34)(35), the majority of these studies have failed to identify downstream effects on the host immune response for the miRNAs detected with altered expression. A major contributing factor to the lack of concrete targets is the use of mixed cell populations or sputum for the identification of differentially expressed miRNAs during M. tuberculosis infection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Wu et al found that miR-155 and miR-155* are potential diagnostic markers that are up-regulated during immune challenge with MtB antigens (Wu et al, 2012). Liu et al also demonstrated that miR-582-5p plays an essential role in regulating anti-MtB directed immune responses by inhibiting monocyte apoptosis as well as down-regulating FOXO1 expression (Liu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%